PENGARUH LATIHAN MENGGUNAKAN GYM BALL TERHADAP NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III - Nurmayanti; Devy Lestari Nurul Aulia (Universitas Batam, 2026)
The prevalence of back pain in pregnant women in Indonesia is 68% with moderate intensity and 32% with mild intensity. Back pain due to pregnancy is a clinical syndrome characterized by pain or discomfort in the back of the body from the last rib to the buttocks or anus. Gym ball exercises in the form of sitting on a ball by shaking the pelvis are considered capable of providing comfort to the lower back through a gate control mechanism. This study aims to determine the effect of training using a gym ball on lower back pain in third trimester pregnant women. The quasi-experiment research method uses a one group pretest posttest without control approach. The research was conducted at the Belat Community Health Center, Karimun Regency from February – August 2024 on 31 pregnant women in the third trimester. Research results The average lower back pain before treatment was 5.29 and after treatment was 1.77. with a p-value of 0.001 (p<0.05) which means there is an effect of training using a gym ball on lower back pain in third trimester pregnant women. It is hoped that pregnant women can apply exercises using a gym ball in the third trimester of pregnancy Keywords: Gymball, Lower Back Pain, pregnant women, third trimester